DIFFICULTIES OF A TERMINOLOGIST. - Tenner, Irving (The Accounting Review, 1941)
The article presents the importance of a common terminology in languages. The author was discussing the handling of municipal expenditures in the operating statements with an official of a large city. Complete agreement was not reached until the official was asked to define "expenditures" and the author discovered that they had been talking about the same thing. This incident illustrates the value of a common terminology, particularly its importance in written communication. For in conversation, if it is not clear what the speaker means, one can question him, but a reader cannot do this. Not only has the value of uniform terminology long been recognized but even the necessity of preparing concise definitions and presenting them in a compilation as one of the means of achieving uniformity is well established. There are two principal classes of terminologies: those prepared for general use and those related to a particular publication. General dictionaries like the Webster's New International Dictionary and the terminologies of the American Institute of Accountants and the Dominion Society of Chartered Accountants are examples of the first class.